New records of West Palaearctic Limoniidae, Pediciidae and Cylindrotomidae (Diptera) from the collections of the Zoological Museum, Amsterdam - Starý, Jaroslav; Oosterbroek, Pjotr (Zootaxa, 2008)
Records of altogether 85 species of the families Limoniidae, Pediciidae and Cylindrotomidae (Diptera) are published, based on the material from the collections of the Zoological Museum, Amsterdam, representing various additions to their distribution in West Palaearctic countries. For Euphylidorea crocotula (Séguy, 1941) a lectotype is designated and figures are provided of male genital structures of this and two other species of Euphylidorea, as well as two species of Gonomyia.